ARSITEKTUR INTERIOR HOTEL SIGNATURE DI BALI - Dewi Lanny Manua; Astrid Kusumowidagdo; Stephanus Evert Indrawan (KREASI, 2016)
Dewsign Interior is an interior design consultant that focus on hotel and hospitality design project. Lead by the founder herself, Dewi Lanny Manua, Dewsign Interior with the help pf experienced staffs are ready to make the best interior and hotel designs that meet the clients expectation. Located in Surabaya, Dewsign Interior provide service to all across Indonesia. Currently Dewsign Interior is working on design project of Signature hotel, Bali. Signature hotel is a three star hotel located at Intan Permai street, Gang Berlian Kerobokan, Badung, Bali. The total land area of this hotel is 2000 m2, with 705 m2 will be designed by Dewsign Interior. With tropical concept and using natural material, this hotel plan to give warm and comfort feelings for all the guests. Dewsign Interior choose the tropical signature concept for this hotel, which is combination from natural material (palimanan stone, jati wood and merbau wood) and the other combination is the shape of the hotel’s logo (celtic maze).